2015
DOI: 10.3402/gha.v8.25912
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition labelling: a review of research on consumer and industry response in the global South

Abstract: BackgroundTo identify peer-reviewed research on consumers’ usage and attitudes towards the nutrition label and the food industry's response to labelling regulations outside Europe, North America, and Australia and to determine knowledge gaps for future research.DesignNarrative review.ResultsThis review identified nutrition labelling research from 20 countries in Asia, Africa, the Middle East, and Latin America. Consumers prefer that pre-packaged food include nutrition information, although there is a disparity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 59 publications
4
56
1
5
Order By: Relevance
“…More than a third of participants indicated that the main reasons for not reading nutrition information on labels were that they 'buy the same type of product all the time' (34.28%) or that they were 'not interested in the nutrition information provided on food labels' (31.44%). These findings are similar to those from a review of research from the global South conducted by Mandle, Tugendhaft, Michalow, and Hofman (2015), who found that a lack of interest in nutrition labelling, time and difficulty in understanding the information were some of the main reasons consumers do not read the nutrition information provided on food labels.…”
Section: Reading Of Nutrition Information On Food Labelssupporting
confidence: 86%
“…More than a third of participants indicated that the main reasons for not reading nutrition information on labels were that they 'buy the same type of product all the time' (34.28%) or that they were 'not interested in the nutrition information provided on food labels' (31.44%). These findings are similar to those from a review of research from the global South conducted by Mandle, Tugendhaft, Michalow, and Hofman (2015), who found that a lack of interest in nutrition labelling, time and difficulty in understanding the information were some of the main reasons consumers do not read the nutrition information provided on food labels.…”
Section: Reading Of Nutrition Information On Food Labelssupporting
confidence: 86%
“…These reasons for ignoring nutrition information on food labels are very similar to those reported in a review conducted by Mandle et al on nutrition labelling in the global South, confirming that consumers, irrespective of their demographic or geographic background, cite similar reasons for not reading the nutrition information on food labels (Mandle, Tugendhaft, Michalow, & Hofman, 2015).…”
Section: Theme 3: Why Do I Ignore the Nutrition Information On Foodsupporting
confidence: 80%
“…Interest in country of origin of a food is understood to be a preference of consumers for foods produced in their own country [19,20], following either from inferences about food quality and safety, or a belief that locally produced foods are better for the local economy. The ranking of important issues on food labels is not consistent across countries [17]. For example, in Ghana the expiration date is ranked first, followed by nutritional information and the ingredient list, with country of origin being ranked as relatively unimportant [21].…”
Section: Discussionmentioning
confidence: 99%
“…The final survey question also returned 14% of people stating they did not use food labels, providing internal consistency for this measure in the survey. It is a common finding that women are more likey to use food labels [17].…”
Section: Discussionmentioning
confidence: 99%